Maternal and Neonatal Factors Associated with Neonatal Mortality: a Prospective Follow-up Study in Selected Hospitals of Nepal - Yadav, Dilip Kumar; Shukla, Girija Shankar; Gupta, Neena; Shrestha, Naveen; Singh, Jitendra Kumar; Kaphle, Hari; Yadav, Pratima; Yadav, Dipendra Kumar (Journal of Nepal Health Research Council, 2024)
Background: Neonatal mortality, a sensitive indicator which indicates the availability, utilization, and effectiveness of maternal and child health services in the community, are major global public health challenges. The objective of the study was to find out the maternal and neonatal factors associated with neonatal mortality in selected hospitals of Nepal. Methods: This was a hospital based prospective follow up study conducted among babies nested for case control study design. Among 1104 babies, 368 babies with LBW and 736 babies with normal birth weight were followed up after 28 days of birth and mortality was assessed. Results: Neonatal mortality was about 10/1000 live birth. In multivariable logistic regression analysis, father with no formal education [AOR:12.54, 95% CI:(2.61-60.13), p=0.002], multi parity [AOR:11.26, 95% CI:(1.25-100.89), p=0.030] and depressed (<7) APGAR score at 5 minutes of birth[AOR:7.44, 95% CI:(1.18-46.80), p=0.032] were significantly associated with neonatal mortality. Conclusions: The study identified ‘father with no formal education, multi parity and low APGAR score at 5 minutes of birth’ as the major contributors to neonatal mortality. Improving parental education, and access to child health care will help to improve neonatal outcome. Keywords: Maternal factors; neonatal factors; neonatal mortality; Nepal.